PENGARUH PENAMBAHAN KATALIS PADA HASIL PENGOLAHAN OLI BEKAS MENJADI BAHAN BAKAR CAIR (BBC) - Saleh, Nurmeizon; Nelvidawati, Nelvidawati; Hartuti, Sri; Azatri, Vina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The use of engine lubricants is increasing every year, so the volume of used oil is also increasing. Based on the Ministry of Environment, used oil belongs to the category of B3 waste. In this research, tests were carried out by adding NaOH to used oil and without adding NaOH to used oil in the processing of used oil into liquid fuel, where the used oil was put into the reactor then heated until the oil in the reactor evaporated and the output was collected, then the physical properties were measured. from the liquid fuel produced where the analysis results using NaOH treatment for the average density value were 831.4 kg/m2, viscosity was 2.24 mm2/s, and the flash point value was 35.1 0C, for analysis results without using the NaOH treatment, the average density value is 831.2 kg/m2, the viscosity is 5.85 mm2/s, and the flash point value is 35.3 0CKeywords : Used Oil, NaOH, Density, Viscosity, Flash Point